Diversité des motivations de la formation et du retour d'étudiants africains de l'Université du Cap-Occidental - Gabriel Tati (Les éditions de la Maison des sciences de l'Homme, 2014)
The article critically examines the experiences of young Africans from west and central Africa who migrate to study in the higher education system of South Africa. These experiences are captured through such aspects as the considerations around the choice of South Africa as a destination, prior attempts to migrate for study in the north, elements that matter in the choice of a south African university where to study and projects of returning home or relocating elsewhere upon completion of study. From a survey conducted at the University of the Western Cape, it emerges that migration of African students is to a large extent a response to the increased inaccessibility in the country of origin to educational programmes carrying good prospects for employment. South Africa provides to African students a viable alternative to studying in their home country affected by persistent crisis of the higher education system. For many students, migration came in the aftermath of a failed attempt to enter a university in the north. The good image of South African higher education system in the continent, the wide range of less costly study programmes and the facilitating mechanisms in place all contribute largely to the act of migration. Students who intend to stay in South Africa are fewer in number than the students planning to leave the country upon completion of study, with the majority contemplating return migration to play a positive role in the development of the home country.